2011
DOI: 10.1111/j.1365-3148.2011.01103.x
|View full text |Cite
|
Sign up to set email alerts
|

Automated washing of human progenitor cells: evaluation of apoptosis and cell necrosis

Abstract: Overall, our data suggest that the automated washing procedure is safe and suitable for processing of thawed HPC-A products and can be daily used in clinical routine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…In our study, we have observed a median percentage of viable CD45+/7‐AAD– and CD45+/CD34+/7‐AAD– cells of 54.93 and 80.55%, respectively. These results are in agreement with the data previously published by our group and by other authors 32‐34. Additionally, we have also observed a positive correlation between the number of total colonies obtained by seeding after thawing and washing procedures of 76 of 96 cryopreserved HPC‐A units and the median percentage of viable CD45+/CD34+/7‐AAD– cells determined through flow cytometric method (r = 0.45).…”
Section: Discussionsupporting
confidence: 93%
“…In our study, we have observed a median percentage of viable CD45+/7‐AAD– and CD45+/CD34+/7‐AAD– cells of 54.93 and 80.55%, respectively. These results are in agreement with the data previously published by our group and by other authors 32‐34. Additionally, we have also observed a positive correlation between the number of total colonies obtained by seeding after thawing and washing procedures of 76 of 96 cryopreserved HPC‐A units and the median percentage of viable CD45+/CD34+/7‐AAD– cells determined through flow cytometric method (r = 0.45).…”
Section: Discussionsupporting
confidence: 93%
“…Using the Sepax‐2, Scerpa et al . obtained TNC and CD34 + recoveries of 91·9% and 86·7%, respectively . Rodriguez et al .…”
Section: Discussionmentioning
confidence: 95%
“…Importantly, similar to Scerpa et al . but unlike others , we defined the cell recovery (%) as the ratio between postwash and prefreeze data so the cell recovery takes into account the cell loss induced by freezing/thawing steps in addition to the washing procedure. Using the Sepax‐2, Scerpa et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may soon change as automated cell washing options, such as Sepax (Biosafe, Eysins, Switzerland), are becoming widely available and have been reported to result in reduced side effects, good cell viability and recovery, as well as comparable neutrophil and platelet engraftment [3, 11, 17-19]. These automated procedures will almost certainly assume a more prominent role in the future but should be studied carefully with regard to the clinical outcome of the recipients.…”
Section: Discussionmentioning
confidence: 99%